PSIKOEDUKASI SEKSUAL TERHADAP REMAJA UNTUK KEFEKTIFITAS PENGETAHUAN TERHADAP PELECEHAN SEKSUAL PADA SMK X RANGKASBITUNG BANTEN - Muhammad Naufal Hafizh (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
The number of crimes of sexual harassment is increasing every year. Due to the increasing number of cases of sexual harassment, it is necessary to anticipate and find solutions to the problem of sexual crimes which are increasing every year, one way to reduce the number of cases of sexual harassment is to prevent it with sexual harassment psycho-education for adolescents. Psychoeducation aims to provide assistance in the form of knowledge and skills to understand and identify what forms and ways to deal with crimes of sexual harassment. So sexual harassment psychoeducation needs to be done to increase knowledge of sexual harassment. The subjects of the research were students of SMK X Rangkas Bitung Banten. This study used a pre-experimental method with a one-group pre-test posttest design. The results of the study showed that there was an increase in knowledge before and after psychoeducation with the mean before (48.92) and after (52.02) with sig 2-(tailed) (0.004). it can be concluded that sexual harassment psychoeducation can provide changes in knowledge to teenagers.